"The Impact of the West": Mustafa Kamil and Juliette Adam, 1895-1908 - Sarfatti, Tami (Jama'a: an Interdisciplinary Journal of Middle East Studies, 1999)
This paper examines the cultural world of Mustafa Kamil as a representative of the Egyptian intellectual elite of the late nineteenth century. Through his relations with Juliette Adam, writer and editor of the La nonvelle revue, and a well-known political-intellectual figure in the Third Republic, this paper offers a new interpretation of the Middle East's "encounter with the West". Conventional historiography described this encounter as a traumatic clash between two essentially oppositional civilizational blocks. This paper, however, argues that the nature of this encounter was more complex and less traumatic. While the world view of Egyptian intellectuals was deeply embedded in the Ottoman-Egyptian-Islamic culture, its members were highly articulate in both oral and written French and felt that French culture was part of their own intellectual world.